Muscular excitation and oxygen extraction responses in power-generating and stabilizing muscles during a graded cycling test - Sendra-Pérez, C.; Encarnación-Martínez, A.; Murias, J. M.; De la Fuente, C.; Salvador-Palmer, R.; Martin-Rivera, F.; Priego-Quesada, J. I. (Journal of Sports Sciences, 2025)
Although some studies have shown an agreement between near-infrared spectroscopy (NIRS) and surface electromyography signals during dynamic exercise for a single muscle, research assessing multiple muscles with different roles is lacking. This would improve understanding of the connection between muscle excitation and muscle oxygen saturation (SmO2) profiles. Our study evaluated whether muscle excitation aligns with SmO2 during cycling in graded exercise testing. Fifteen cyclists and triathletes (age = 22 ± 6 years, stature = 175 ± 8 cm, training hours = 12 ± 4 hours·week-1) performed a graded exercise test on a cycle ergometer. NIRS and electromyography devices were placed on the preferred sides of the vastus lateralis, tibialis anterior, gastrocnemius medialis, and biceps femoris. Results showed that, in general, while average root mean square (RMS) increased, SmO2 decreased (p < 0.05), except in the gastrocnemius medialis, which remained stable. Vastus lateralis and biceps femoris exhibited moderate signal agreement between RMS and SmO2 (CCCLin: vastus lateralis = 0.70; biceps femoris = 0.50), while stabilizing muscles showed weak agreement (gastrocnemius medialis CCCLin = 0.32; tibialis anterior CCCLin = 0.39). In conclusion, power-generating and stabilizing muscles respond oppositely in SmO2 and RMS during progressively increasing intensity exercise until exhaustion.